Impact of enteral nutrition initiated within 24 h of ECMO on nutritional status and inflammatory response in children - Ren, Ye; Lu, Siwei; Chen, Yingfu; Sun, Yuelin; Fu, Yueqiang; Liu, Chengjun; Li, Jing; Dang, Hongxing (Frontiers in Pediatrics, 2025)
ObjectiveMalnutrition remains a significant issue in children undergoing ECMO. This study aimed to investigate the effects of initiating enteral nutrition (EN) within 24 h on the adequacy of nutrient intake, nutritional status, anabolic metabolism, and inflammatory markers in children receiving ECMO.MethodsThis was a prospective observational cohort study, including children receiving ECMO therapy at the Children's Hospital of Chongqing Medical University of China from April 2018 to August 2024. Patients were divided into early EN (EEN) and late EN (LEN) groups based on whether effective EN was initiated within 24 h after the start of ECMO. T-tests or Mann–Whitney U and Chi-square tests were used to compare the clinical characteristics, serum total protein (TP), nutritional intake, serum cholinesterase (CHE), and C-reactive protein (CRP) levels between the two groups. Linear mixed-effects models (LME) were applied to assess the effect of EEN on changes in CRP and CHE levels over time during ECMO.ResultsA total of 47 children were included in this study, with 24 patients (51.1%) successfully receiving EEN. The PRISM3 score was higher in the LEN group (P = 0.016). The majority of children in the EEN group had pneumonia or ARDS (P < 0.001). The average daily energy and protein intake, as well as their adequacy, was higher in the EEN group compared to the LEN group (P < 0.001), although the EEN group experienced more frequent interruptions in EN (P < 0.05). Serum TP levels in the EEN group were higher than those in the LEN group during the first 3 days of ECMO (P < 0.05). The median CHE levels were higher, and the median CRP levels were lower in the EEN group compared to the LEN group (P < 0.05). LME analysis showed a significant interaction effect between EEN and time on CRP and CHE levels (P < 0.001).ConclusionSuccessfully initiating EN within 24 h significantly improves the nutritional status of children receiving ECMO, promotes hepatic anabolic metabolism, and reduces inflammatory responses. This study provided new insights and data support for nutritional therapy strategies in children on ECMO.